2020
DOI: 10.1002/adsu.202000096
|View full text |Cite
|
Sign up to set email alerts
|

Toward Commercial Carbon Dioxide Electrolysis

Abstract: The electrochemical carbon dioxide reduction reaction (ECDRR) driven by clean energy resources (such as wind, solar, etc.) to chemical feedstock and fuels is an attractive route to balance the carbon‐neutral cycle and for regenerating fuels. To date, the ECDRR has been the most promising technology for the conversion of carbon dioxide (CO2) to carbon‐building blocks, which has a huge market demand and increasing annual global production. Despite tremendous research, the conversion of CO2 into valuable fuels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 175 publications
0
27
0
Order By: Relevance
“…However, the high energy consumption of such a process makes it problematic to carry out using conventional chemical approaches, and the most attractive is the possibility of electrochemical reduction of CO 2 . Several recent publications are devoted to this problem, including reviews [155][156][157][158][159][160][161][162][163][164][165]. It should be noted that membrane technologies play an important role in these processes [155].…”
Section: Electrochemical Technologies For Co 2 Capture and Processingmentioning
confidence: 99%
“…However, the high energy consumption of such a process makes it problematic to carry out using conventional chemical approaches, and the most attractive is the possibility of electrochemical reduction of CO 2 . Several recent publications are devoted to this problem, including reviews [155][156][157][158][159][160][161][162][163][164][165]. It should be noted that membrane technologies play an important role in these processes [155].…”
Section: Electrochemical Technologies For Co 2 Capture and Processingmentioning
confidence: 99%
“…Among the CO 2 mitigating technologies, CO 2 conversion is an attractive approach that could reduce the global energy crisis by transmuting CO 2 into valueadded chemical molecules and energy fuels using renewable energy means [5][6][7]. Presently, CO 2 conversion can be divided into electrochemical, photochemical, and thermochemical technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The achievements to date in ECR technology are very promising and scientific community is paying much attention towards its development. Most research studies have discussed the reaction mechanism of electrocatalysts and their underlying working principles, whereas others have concentrated on the improvement of bench-scale EC cells for efficient CO 2 reduction [7]. Nevertheless, very few research studies have been reported to com-prehend the viability of ECR technology as a way of producing chemicals and fuels on techno-economic grounds and what factors can affect its commercialscale utilization.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] In particular, the electrocatalytic CO 2 reduction reaction (ECR) in aqueous media is extremely interesting in terms of multiple merits—low cost, sustainable, easy to handle—which can be applied commercially. [ 3–7 ] CO 2 can be reduced to various gaseous as well as liquid products such as CO, C 2 H 4 , CH 4 , C 2 H 5 OH, CH 3 OH, and so on. [ 8 ] The energy values (current market price per energy unit) of CO of ECR are the highest valuation among other gaseous products such as methane and ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] To assess technological ECR reaction, high activity, selectivity, and productivity are required. [ 6 ] Furthermore, a wide potential/current range would sustain the ECR electrocatalysis at commercial level while remaining highly selective ECR reaction. Thus, developing efficient electrocatalysts especially for CO 2 ‐to‐CO reduction, which are able to preserve their high selectivity under wide potential/current window, is highly desirable.…”
Section: Introductionmentioning
confidence: 99%